Application of double filtration with granular activated carbon for Atrazine reduction on water treatment processes (2018)
Atrazine is one of the most often used herbicides in the world. It reaches the surface water body by runoff, direct application or airborne dispersal. Conventional water treatment methods do not efficiently remove these types of pollutants, whereas granular activated carbon (GAC) adsorption is an adequate technique for the removal of organic compounds from water. In this work, the Atrazine reduction of water doped with two concentrations of Atrazine, was evaluated during the conventional treatment process (coagulation, flocculation, sedimentation and sand and anthracite filtration), followed by double filtration with two adsorbent granular media (vegetal and mineral GAC), which resulted in an efficient reduction of UV254 (86%) and Atrazine (99%).